Immunogenicity of BNT162b2 mRNA SARS-CoV-2 vaccine in patients with psoriatic arthritis on TNF inhibitors. Issue 1 (5th January 2022) - Venerito, Vincenzo; Stefanizzi, Pasquale; Fornaro, Marco; Cacciapaglia, Fabio; Tafuri, Silvio; Perniola, Simone; Iannone, Florenzo; Lopalco, Giuseppe
Abstract : Background: Scanty data on the immunogenicity of the BNT162b2 vaccine in patients with psoriatic arthritis (PsA) on Tumor Necrosis Factor inhibitors (TNFi) have been published. Objective: To investigate the humoral response to BNT162b2 vaccination patients with PsA on TNFi, comparing immunogenicity with healthy controls. Methods: Forty patients with classified PsA on TNFi undergoing vaccination with the BNT162b2 mRNA SARS-CoV-2 vaccine (BioNTech/Pfizer) were enrolled. Fifteen days after the second shot, serum IgG levels against SARS-CoV-2 (Abbott ARCHITECT i2000SR, positivity cut-off 50 AU/mL) were assayed in all patients. Clinimetrics and treatment data were gathered. TNFi treatment was not discontinued throughout the whole period, whereas methotrexate (MTX) was discontinued for 1 week after each shot in those on combination therapy. Sera from healthcare professionals were considered as healthy controls for 1:1 propensity score matching; any of them was taking medication. Student's t-test and logistic regression were used for investigating differences in immunogenicity between groups and predictors of antibody response. Results: Clinical Disease Activity Index did not change before and after vaccination (7.06±5.23 to 7.10±5.27, p=0.92). Patients with PsA achieved a positive anti-SARS-CoV-2 IgG level with a mean (±SD) of 13794.44±15 815.42 AU/mL. Although lower, the antibody level was not significantly different from matched controls (19227.4±11.8460.45 AU/mL, p=0.08). In the overall sample, those on MTX (12/80, 15%) had a trend toward lower immune response (p=0.07); glucocorticoid therapy (11/80, 13.8%) predicted lower antibody levels (p=0.04). Conclusions: Continuing TNFi in patients with PsA throughout the vaccination did not hamper immunogenicity.